An inventory of glacial lakes in the Third Pole region and their changes in response to global warming - Zhang, Guoqing; Yao, Tandong; Xie, Hongjie; Wang, Weicai; Yang, Wei (Global and planetary change, 2015)
No glacial lake census exists for the Third Pole region, which includes the Pamir-Hindu Kush-Karakoram-Himalayas and the Tibetan Plateau. Therefore, comprehensive information is lacking about the distribution of and changes in glacial lakes caused by current global warming conditions. In this study, the first glacial lake inventories for the Third Pole were conducted for ~1990, 2000, and 2010 using Landsat TM/ETM+ data. Glacial lake spatial distributions, corresponding areas and temporal changes were examined. The significant results are as follows. (1) There were 4602, 4981, and 5701 glacial lakes (>0.003km2) covering areas of 553.9±90, 581.2±97, and 682.4±110km2 in ~1990, 2000, and 2010, respectively; these lakes are primarily located in the Brahmaputra (39%), Indus (28%), and Amu Darya (10%) basins. (2) Small lakes (<0.2km2) are more sensitive to climate changes. (3) Lakes closer to glaciers and at higher altitudes, particularly those connected to glacier termini, have undergone larger area changes. (4) Glacier-fed lakes are dominant in both quantity and area (>70%) and exhibit faster expansion trends overall compared to non-glacier-fed lakes. We conclude that glacier meltwater may play a dominant role in the areal expansion of most glacial lakes in the Third Pole. In addition, the patterns of the glacier-fed lakes correspond well with warming temperature trends and negative glacier mass balance patterns. This paper presents an important database of glacial lakes and provides a basis for long-term monitoring and evaluation of outburst flood disasters primarily caused by glacial lakes in the Third Pole. •The first glacier lake inventory across the Third Pole was developed.•Glacial lakes were primarily located in Brahmaputra (39%), Indus (28%), and Amu Darya (10%) basins.•Glacier-fed lakes showed faster expansion than non-glacier-fed lakes.•Glacier-melt water may play a dominant source for most glacial lake expansion from 1990–2010.